HOW SPELLING IN ENGLISH AS A SECOND LANGUAGE AFFECTS THE ACADEMIC PERFORMANCE OF FIRST YEAR STUDENTS AT THE UNIVERSITY OF NAMIBIA - Frieda Ndapewa Namugongo,; Dr Nchindo Mbukusa, (IJRDO- Journal of Educational Research, 2019)
The perplexities of spelling in a Second Language against the First (Mother Tongue) has complicated situations in subjects that are taught in English as a Second Language in Namibian schools including the University of Namibia.  The complexities on students unfortunately shift to the lecturers as students struggle with /r/ and /l/ in ‘pray and play’ as numerous mother tongues in Namibia have fossilized errors that mix the two.  It is observed that first year students at the University of Namibia have numerous spelling mistakes that hamper both teaching learning.  This study therefore aims at finding out the causes and effects of such errors on teaching and learning among mixed Second Language and First language students and lecturers who seek to find ways to solve the situation. A qualitative study, designed from phenomenology, through semi-structured interviews, deeply investigated six students and four lecturers teaching English for Academics at the University of Namibia. Amongst many, results show that students face language interference, ignorance, transfer of words from another language to English, false analogy, lack of interest in reading wide among students and exposure (post school activities, parent’s educational background, major language spoken at home) and carelessness.  There is need for lecturers to incorporate fun activities in their lectures that cover spelling. Lecturers should also be encouraged to consider various strategies that assist students with spelling.